2020
DOI: 10.1088/2399-6528/ab6fb4
|View full text |Cite
|
Sign up to set email alerts
|

Monogamy of correlations and entropy inequalities in the Bloch picture

Abstract: We investigate monogamy of correlations and entropy inequalities in the Bloch representation. Here, both can be understood as direct relations between different correlation tensor elements and thus appear intimately related. To that end we introduce the split Bloch basis, that is particularly useful for representing quantum states with low dimensional support and thus amenable to purification arguments. Furthermore, we find dimension dependent entropy inequalities for the Tsallis 2-entropy. In particular, we p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…The systematic investigation of the properties of the Bloch representation for finite-dimensional multi-party quantum systems is a relatively recent subject [4][5][6][7][8][9][10][11][12][13][14][15], although many important results were found earlier, mostly relating specific features of the Bloch picture to the entanglement properties of the state (e.g., [16][17][18][19][20][21][22][23][24][25][26]). Currently much activity is devoted to working out the technical details and properties for an easier use of the Bloch representation to solving physics problems.…”
Section: Introductionmentioning
confidence: 99%
“…The systematic investigation of the properties of the Bloch representation for finite-dimensional multi-party quantum systems is a relatively recent subject [4][5][6][7][8][9][10][11][12][13][14][15], although many important results were found earlier, mostly relating specific features of the Bloch picture to the entanglement properties of the state (e.g., [16][17][18][19][20][21][22][23][24][25][26]). Currently much activity is devoted to working out the technical details and properties for an easier use of the Bloch representation to solving physics problems.…”
Section: Introductionmentioning
confidence: 99%
“…As a direct consequence of these results we derive several interesting relations for the reductions of rank-1 operators. As the Schmidt decomposition, the existence of relations for one-party reductions, and the Bloch representation [15][16][17][18][19][20][21][22] of bipartite quantum states are intimately related concepts [19,21,23], we conclude our discussion by analyzing the most salient of these mathematical connections.…”
Section: Introductionmentioning
confidence: 94%
“…[2,3] or to find new independent monogamy relations, see, e.g., Refs. [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. Furthermore, it was found that also correlations other than entanglement, such as nonlocality, may obey monogamy relations [21][22][23].…”
mentioning
confidence: 99%
“…Note that the linear entropy is proportional to the Tsallis 2-entropy [29,48] and has a simple functional relation with the Rényi α-entropy for α = 2 [49]. To date, only few inequalities are known for the linear entropy [6,15,19,29,50].…”
mentioning
confidence: 99%
See 1 more Smart Citation